The Typical Different Features of Grammar of the British English (BrE) and American English (AmE) - I Wy Dirgeyasa (Universitas Cokroaminoto Palopo, 2016)
There are a number of varieties of English all over the world such as American, British, Australian, Indian, Singaporean, Philippine English, etc. However, there are only two varieties of English which are most widely and dominantly taught, learned, and used both spoken and printed around the world namely British English (BrE) and American English (AmE). In real sense, the two are often confusing for the non-native learners because they have some differences and uniqueness in some aspects such as spelling, pronunciation, vocabulary, and grammar. Therefore, it is really important for students, teachers and speakers as well to be aware of the major differences between the two. This paper is trying to review some striking unique and different features of grammar of British English (BrE) and American English (AmE).